OK, Boomer: New Users, Different Platforms, New Challenges - Luis M. Romero-Rodríguez; Santiago Tejedor; Inmaculada Berlanga (Media and Communication, 2022)
The popularization of new interaction spaces brings new narratives and social phenomena that merit attention from the scientific community. Based on the existing literature on the new challenges facing the communication discipline with these emerging narratives, this editorial summarizes the empirical and theoretical contributions of the thematic issue entitled “New Narratives for New Consumers: Influencers and the Millennial and Centennial Generations.” The authors emphasize that the studies selected for this thematic issue explore the innovative features and opportunities of the emerging scenarios and offer a cautionary account of their structural problems and the urgency of a new media literacy.